Volume changes at Santiaguito volcano between 2011 and 2019 based on TanDEM-X InSAR data - Edrich, Ann-Kathrin; Kubanek, Julia; Gottschämmer, Ellen; Duckstein, Alexandra; Westerhaus, Malte; Kowalski, Julia; Rietbrock, Andreas (Frontiers in Earth Science, 2025)
The Santiaguito volcanic dome complex in Guatemala consists of four volcanic domes formed within the 1902 eruption crater of Santa María volcano, with only the oldest dome, Caliente, currently active. Caliente is characterized by frequent explosive eruptions, rockfalls, pyroclastic flows, and blocky lava flows. TanDEM-X data enable the generation of high-resolution digital elevation models of complex volcanic terrain. Repeated acquisitions over the same area allow for the detection and quantification of topographic changes associated with volcanic activity. This study investigates elevation and volume changes at Caliente’s southern flank and western crater region from September 2011 to April 2019 using 24 TanDEM-X-derived digital elevation models with spatial resolutions of 6.5 m (N–S) and 4 m (E–W). Between 2011 and 2016, several new lava flows were emplaced on the southern flank, while the crater region experienced a volume decrease of (545±4)⋅103m3. From 2016 to 2019, significant dome growth increased the volume in the crater region again by (354±3)⋅103m3, primarily in the center. Concurrently, volume decreased along the northwestern crater rim, likely due to the 2016 explosive eruption. The average volume output rate over the entire observation period is calculated as 0.18±0.0004m3/s. The results align with previously determined cyclic patterns at Santiaguito volcano and provide a qualitative and quantitative description of the behavioral shift during our period of observation.